Efectos del entrenamiento cruzado vs el entrenamiento tradicional sobre la composición corporal y Vo2 pico en mujeres y hombres de 18 a 45 años de edad sometidos a ocho semanas de entrenamiento en el Centro de Acondicionamiento Físico Ultra Wellness Center (2019)
The World Health Organization (WHO) figures show that the world population is increasing chronic non-communicable diseases (CNCDS), such as obesity, hypertension, atherosclerosis and type II diabetes mellitus; leading to increased cardiovascular disease (EC), representing the leading cause of death worldwide. The interventions in physical activity have been shown to have effects on the body composition and the VO2, variables that seem to decrease the cardiovascular risk, however the most efficient load parameters, are still in discussion, therefore arises the Question about the effects of cross-training vs. traditional training on body composition and peak Vo2 in women and men 18 to 45 years of age subjected to 8 weeks of training at the Ultra Wellness Center Fitness Center. Methodology: Study of experimental cut simple blind and parallel, approved by the Ethics Committee of the University San Buenaventura Medellin. The intervention was carried out in 2 groups randomised and subjected to 8 weeks of intervention, in cross and traditional training; We analyzed variables such as Vo2 Pico, and body composition. Sample size calculation was performed through EPIDAT version 4.0 and pre and post statistical data were analyzed through SPSS V. 21 Software Results: There were No differences between the statistically significant groups in the population before the intervention; indicating that the basal variables were homogeneous, later on the intervention found significant differences in the abdominal perimeter variable, > P = 0.05 of the cross training individuals who decreased 2 centimeters After 8 weeks of intervention; However, the body composition variable did not have statistically significant changes